Translation of the efficacy of antibody-drug conjugates from preclinical to clinical using a semimechanistic PK/PD model: A case study with RC88 - Qiaoning Li; Ling Wang; Jinfeng Zhang; Guorui Zhao; Zhihao Liu; Xinting Ma; Jing Jiang (Wiley, 2023)
Abstract Three semimechanistic pharmacokinetic/pharmacodynamic (PK/PD) models, Simeoni, Jumbe, and Hybrid, were used for the efficacy translation of RC88 from preclinical to clinical. RC88 is a mesothelin‐targeting antibody-drug conjugate for malignant solid tumor. In the preclinical study, the relationship between PKs and PDs was determined using the xenograft mouse model derived from ovarian cancer and lung cancer cell lines. A secondary parameter representing the efficacy index of the drug, termed as tumor static concentration (TSC), was calculated using the three semimechanistic PK/PD models. A mechanism‐based target‐mediated drug disposition model was used to predict the human PKs. TSC from mice and predicted human PK were integrated to predict human efficacy dose. Results showed that 2 cell lines were sensitive to drugs, and the predicted efficacy dose was between 0.82 and 1.96 mg/kg q1w.